DUKUNGAN KELUARGA TERHADAP KUALITAS HIDUP ODHA : LITERATURE REVIEW - Muhammad Al-Amin R. Sapeni Sapeni; Toar Calvin Christo Paat; Yeni Iswari; Helmi Juwita (Jurnal Mitra Kesehatan, 2023)
Introduction: HIV-AIDS is a disease that can be transmitted and has high morbidity and mortality rates and is still a health problem at the global level. To improve the quality of life of PLWHA, treatment and family support are needed. However, some phenomena show the opposite, thus affecting the quality of life and the treatment process. This study aims to identify family support for the quality of life of PLHIV. Methods: The study design used literature review by searching 3 electronic databases, namely Pubmed, ScienceDirect, and Google Scholar. Research questions used the PICO method, and keywords with Boolean searches (HIV/AID patients OR HIV/AIDS patients) AND (Family support OR Family support OR Support System) AND (Improve Quality of Life OR Improve Quality of Life). The inclusion criteria used were (1) focusing on patients with HIV/AIDS (2) search techniques using PICO and Bolean (3) published in English and Indonesian (4) including articles of the type of intervention such as Randomized Controlled Trial (RCT), Quasy Experiment , Cohot, Case Control and the like (5) published in the last 10 years (6) articles using a questionnaire instrument. There were 2838 articles from 3 databases and only 8 articles were included in this study, namely articles with analytic descriptive and observational research. Results: A total of 8 articles met the inclusion criteria. Of the several articles, there were 884 PLHIV involved in this study, 7 articles were included using a cross-sectional approach, the rest used a cohort study approach. Conclusion: Family support is related to the quality of life of PLHIV patients and can improve the quality of life. So it can be recommended to be part of the patient's care.